Caligrafia marginal: pichação, performance e patrimônio - Rodrigues, Livia Nunes Borges (2015)
This research does a general approach about the urban interventions, giving priority to the actions ephemeral (graffiti and pichação), how arise each of these practices, their disparities in Brazil, and the actions taken by the Government for combat them, with enphasis in pichação. The pichação is a practice of marginal and oppositional character that has become an integral part of complex societies. For the government, as well as for a large portion of Brazilian society that action is taken as a crime, but for those who are included in this marginal culture, the act of tagging can be interpreted as a socialization tool communication, leisure, art, call to memory etc. Among the various perspectives of analysis contained in pichação, this work sought to explore how this urban offensive action can be interpreted under the bias of performative act. In addition, it sought to understand how graffiti artists and other residents of Goiânia/GO, deal with the elements arranged in the urban space, emphasizing the architectural constructions of social value.